DICHLORODIPHENYLTRICHLOROETHANE (DDT) POISONING: A CASE REPORT - KAUR, CHANDANDEEP; MITTAL, MANSI; SINGH, JASKIRAT (International Journal of Current Pharmaceutical Research, 2026)
Objective: Dichlorodiphenyltrichloroethane (DDT) is a highly lipophilic organochlorine pesticide known for its environmental persistence and neurotoxicity. Although banned or restricted in many countries, sporadic cases of poisoning continue to occur due to illegal use and accidental exposure. Acute toxicity primarily affects the nervous system. Methods: We report a case of acute DDT poisoning in a 34 y old male who presented with gastrointestinal and neurological symptoms following accidental ingestion. The patient initially had stable vital parameters but subsequently developed respiratory failure and hypotension requiring mechanical ventilation and vasopressor support. Management was entirely supportive, as no specific antidote exists for DDT toxicity. Results: The patient showed progressive clinical improvement and was successfully extubated on the third day, with complete recovery. Conclusion: DDT poisoning, though uncommon, should be considered in patients presenting with unexplained neurological manifestations and a relevant exposure history. Early recognition and aggressive supportive management are crucial for favorable outcomes.